Age and growth of a highly successful invasive species: the Manila clam Ruditapes philippinarum (Adams & Reeve, 1850) in the Tagus Estuary (Portugal) - Moura, Paula (2018)
The Manila clam Ruditapes philippinarum (Adams & Reeve, 1850) was introduced in several regions worldwide where it is permanently established. In Portuguese waters, the colonisation of the Tagus Estuary by this invasive species coincided with a significant decrease in abundance of the native Ruditapes decussatus (Linnaeus, 1758). This study aimed to estimate the age and growth of the Manila clam, to compare the growth performance between R. philippinarum and R. decussatus in several locations worldwide, and to ascertain whether the Manila clam's growth patterns contributed to the extensive distribution of this invasive bivalve in the Tagus Estuary. The growth of R. philippinarum in the Tagus Estuary was described through the von Bertalanffy equation SLt=65.2[1-e(-0.34(t+0.93))],corresponding to a phi-prime index (phi') of 3.160 and an overall growth performance of 4.974. This growth performance is the second highest recorded for R. philippinarum worldwide and was much higher than that of R. decussatus from Portugal. This study confirmed that the Tagus Estuary presents near-ideal environmental conditions for growth of the Manila clam. R. philippinarum displayed clearly invasive behaviour, spreading widely and growing faster than the native R. decussatus, which certainly contributed to the decline of its populations in the Tagus Estuary.